Pengaruh Jumlah Uang Beredar dan Sertifikat Bank Indonesia Syariah (SBIS) Terhadap Indeks Saham Syariah Indonesia (ISSI) dengan Nilai Tukar Rupiah Sebagai Variabel Moderasi Periode 2016-2021 - Irfani Utami Putri Aidin; Fil Isnaeni (Yayasan Literasi Ilmiah Indonesia, 2023)
The study aims to determine the effect of the money supply on the Indonesian Sharia Stock Index moderated by the exchange rate. To find out the effect of Bank Indonesia Sharia Certificates on the Indonesian Sharia Stock Index moderated by the exchange rate. The research method used is the multiple linear regression model with e-views, with data collection techniques using the documentation study method (documentary research) and secondary data obtained from the website of Bank Indonesia, the website of the Central Statistics Agency and the website of the Indonesia Stock Exchange. The hypothesis uses the classical assumption test, multiple linear regression equations, partial test (t test), simultaneous test (F test) and the coefficient of determination. The results of this study indicate that partially the Amount of Money in Circulation has no effect and is not significant on the Indonesian Sharia Stock Index, Bank Indonesia Sharia Certificates have an influence and is significant on the Indonesian Sharia Stock Index, the money supply on the Indonesian Sharia Stock Index has no effect and is not significantly moderated by exchange rate, Sharia Bank Indonesia Certificate with Indonesia Sharia Stock Index influential and significantly moderated by the exchange rate. Keywords: Money Supply, Indonesian Sharia Stock Index, Bank Indonesia Sharia Certificates, exchange rates